Wnt Signaling Drives Correlated Changes in Facial Morphology and Brain Shape - Marchini, Marta; Hu, Diane; Lo Vercio, Lucas; Young, Nathan M.; Forkert, Nils D.; Hallgrímsson, Benedikt; Marcucio, Ralph (Frontiers in Cell and Developmental Biology, 2021)
Canonical Wnt-signaling plays multiple roles critical to normal craniofacial development while its dysregulation is known to be involved in structural birth defects of the face. However, when and how Wnt signaling influences phenotypic variation, including those associated with disease, remains unclear. One potential mechanism is via Wnt signaling’s role in the patterning of an early facial signaling center, the Frontonasal Ectodermal Zone (FEZ), and its subsequent regulation of early facial morphogenesis. For example, Wnt-signaling may directly alter the shape and/or magnitude of expression of the Sonic hedgehog (SHH) domain in the FEZ. To test this idea, we used a replication-competent avian sarcoma retrovirus (RCAS) encoding Wnt3a to modulate its expression in the facial mesenchyme. We then quantified and compared ontogenetic changes in treated to untreated embryos in the three-dimensional (3D) shape of both the sonic hedgehog expression domain of the FEZ,and the morphology of the facial primordia and brain using iodine-contrast microcomputed tomography imaging and 3-dimensional geometric morphometrics (3DGM). We found that increased Wnt3a expression in early stages of head development produces correlated variation in shape between both structural and signaling levels of analysis. In addition, altered Wnt3a activation disrupted the integration between the forebrain and other neural tube derivatives. These results show that activation of Wnt signaling influences facial shape through its impact on the forebrain and SHH expression in the FEZ, and highlights the close relationship between morphogenesis of the forebrain and midface.